2015
DOI: 10.4103/0975-5950.168213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ultrasonography as a diagnostic tool in the management of head and neck facial space infections: A clinical study

Abstract: Introduction:Superficial facial space infections represent a significant amount of the dental problems that present to hospital. Determining whether an odontogenic swelling is a cellulitis or abscess is difficult, but important as both may require different treatments. The use of an ultrasound may aid in differentiating cellulitis and abscess. This study was done to compare the accuracy of clinical examination alone versus ultrasonography (USG) in the diagnosis of cellulitis and abscess in symptomatic patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
3
5
0
8
Order By: Relevance
“…Analysis with SPSS software found that USG precisely distinguished 84% of all included fascial spaces and 100% of included superficial spaces. These results were in near approximation to previous studies[ 4 , 5 , 18 , 19 ]. One previous study showed a significant association between histological findings and ultrasonography of oral maxillofacial swelling[ 20 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis with SPSS software found that USG precisely distinguished 84% of all included fascial spaces and 100% of included superficial spaces. These results were in near approximation to previous studies[ 4 , 5 , 18 , 19 ]. One previous study showed a significant association between histological findings and ultrasonography of oral maxillofacial swelling[ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have involved differentiating cellulitis from abscesses by clinical examination and USG. The diagnosis was correct 68% of the time with clinical examination alone and 70% of the time using clinical examination plus USG[ 5 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Shah et al 10 found that ultrasound was a useful adjunct to clinical examination in differentiating cellulitis from an abscess. Several other studies have also shown that ultrasound is a reliable tool in detecting pus in the head and neck [11][12][13] with a sensitivity of 96% and specificity of 82%.…”
Section: Discussionmentioning
confidence: 98%
“…32,33 Ultrasound can be used to assist the clinical assessment of infections, including cellulitis, and help determine if the infection extends into the deeper layers. [34][35] Cellulitis is often seen sonographically as a poorly defined hyperechoic signal within the subcutaneous tissue. The neighboring deeper tissues should be inspected for potential involvement.…”
Section: Systematic Approach To Musculoskeletal Ultrasound After Pomentioning
confidence: 99%